PENGARUH KETERPUTUSAN POLA ASUH ORANGTUA TERHADAP PENDIDIKAN ANAK - Aufia Aisa, M. Mujabun (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
Intellectual development in the life of a teenager must be balanced with good values, morals and morals. Children who do not have a harmonious relationship with their parents in childhood are unlikely to be able to develop super egos that are strong enough, so they can be people who often violate social norms. Independence and moral maturity always put forward in every behavior in every life. The ability that exists in a child's life makes them able to have good morals and attitudes in the future. A person's basic personality is formed in childhood. The processes of development that occur in a child coupled with what is experienced and accepted during the time of his children gradually enable him to grow and develop into an adult human. It is hoped that parents can get to know the growth and development of their sons and daughters as early as possible to find the possibility of abnormalities or deviations in development. The existence of cooperation and a joint approach by experts from various sciences and activities will greatly help the development of children. And the most important point is the parents who are most responsible in developing the overall existence of children, including here physical and psychological needs, so that children can grow and develop towards a harmonious and mature personality.